FORMULATION OF PLANT BASED SANITIZER AND ITS EVALUATION - Vikrant Verma1, Parkhi Rastogi2,Saurabh Singh3,Aakash tyagi4,Abhishek Sharma4,Aasif Rao4,Ganesh Prasad Mishra1, (Chelonian Research Foundation, 2023)
Preparartion of alcohol free hand sanitizer with antimicrobial qualities is essential, particularly in pandemics where there is a low supply chain and high demand for ethanol and isopropanol. Preparing sanitizer using natural ingredients that are effective against a wide range of pathogens was the aim of this study. The outcomes demonstrated that prepared sanitizer were deemed to have acceptable organoleptic properties. The formulation pH was slightly acidic (about 3.8) because aloe vera, which has an acidic reputation, was present in large amounts (90% v/v). The results of the antimicrobial effectiveness test showed that the sanitizer that were prepared exhibited antimicrobial activities against a variety of gram-positive and gram-negative bacteria as well as the yeast Candida albicans. Twenty human volunteers participated in an acceptability study, which revealed that the hand sanitizer did not cause any symptoms of skin irritation. The prepared natural sanitizer may serve as a viable substitute for the widely used alcohol-based hand sanitizers according to this study. Keywords: Alcohol, Sanitizer, Microorganisms, Infections, Essential Oils, Antimicrobial, Pandemics